Both Acute and Chronic Exercise Decrease Total Cholesterol Level in Human Blood - Bambang Purwanto; Wahyu N. Pratiwi; Abdurachman Abdurachman (Humanistic Network for Science and Technology (HNST), 2018)
Exercise such as Diabetes dance of Persadia 1 is the evolvement of prior diabetes dance series with aerobic principle with more eccentric movement. Diabetes dance of Persadia 1 has been inspected effective for lowering fasting blood glucose, but its still unknown about its effect on blood level of total cholesterol. The aim of this research was to analyze the effect of exercise on total cholesterol level. This research was experimental study, with 16 subject of healthy housewifes and divided on 2 groups, that were exercise and control group. Exercise group was given with diabetes dance of Persadia 1 while control group have the unstructured activity. Blood level of total cholesterol (TC) has been measured after 24 hours post single bout exercise (acute-AE) and repeated exercise (chronic exercise-CE). Paired t-test analysis on both acute (AC) (p=0.005) and chronic (CC) (p=0.006) shows TC decrease significantly on control group, as well as on AE (p=0.001) and CE (p=0.001). However, TC tend to increase on CC though not significantly increase (p=0.916), while on CE tend to decrease significantly (p=0.041). This study showed that both acute and cronic exercise decrease total cholesterol level in human blood. Keywords: Interleukin-6, Total cholesterol level, Exercise